دراسة تنوع البنى الحراجية في محمية الفرنلق - الشاطر, زهير; بلال, عماد; قازنجي, فادي (Latakia University Journal -Biological Sciences Series, 2019)
تمت دراسة التنوع البنيوي للمجموعات الحرجية في محمية الفرنلق شمال اللاذقية خلال العام 2008 وذلك اعتباراً من 52 عينة مساحة كل منها 100م2 وباستخدام طريقة تحليل المكونات الأساسية والتحليل العنقودي حيث أمكن تحديد ست بنى أساسية بالاعتماد على الكثافة الشجرية, التغطية الطابقية, القطر المتوسط والارتفاع السائد كما أظهرت الدراسة تنوعاً واضحاً في صفوف الأقطار في المجموعات الحرجية المدروسة. تعتبر النتائج التي تم الحصول عليها مهمة وتؤسس لمتابعة البحث في هذا المجال. Structural diversity of forest stands has been studied in Al-Foronloq protected area in Lattakia during 2008 from 52 plots of 100m2, utilizing the Principal Component Analysis and the Cluster Analysis. Six basic structures have been defined depending on the trees' density, stage covering, diameter average, and dominant height. The study has also showed an important diversity in the diameter classes in these stands. The obtained results are very important for the future research in this domain.